Moodle LMS: Positive and Negative Aspects of Using Distance Education in Higher Education Institutions - Evgenievich Egorov, Evgeny (2021)
The Moodle learning management system (LMS) is currently successfully integrated into the educational activities of higher education. This article discusses the peculiarities of Moodle LMS and elements of training courses in it. The research aims at highlighting the assessments of opportunities and disadvantages of the Moodle LMS from the positions of undergraduate students and teachers in the quarantine conditions and before them. The research was conducted at the Kozma Minin Nizhny Novgorod State Pedagogical University in 2018/2019 and 2019/2020 academic years at the Faculty of Management, Social and Technical Services. The research involved teachers and first to fourth year full-time undergraduate students. The analysis of both positive and negative feedback from undergraduate students and teachers about working in a normal learning model and in self-isolation has been presented. Interactive elements of the learning environment have been considered and the research results of students' attitudes to its various elements have been described. The methods and potential use of Moodle by means of different electronic devices have been explored, and the usage frequency of these devices during quarantine has been analyzed. The analysis of negative feedback about the students’ and teachers’ work in the system during the pandemic has been given. Control methods in the Moodle environment, testing, and authors’ control methods have been studied. In the survey, the respondents evaluated the basic functions of the Moodle LMS, popular in teaching, gave a description of the advantages and disadvantages of this system and evaluated potential areas of system development in educational practice of the University. The conclusions have been made about the need to implement blended learning using the Moodle LMS, which combines various types of distance and classroom work for students.